FAKTOR PENYEBAB PERKAWINAN TIDAK TERLAPOR DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BONE BOLANGO - NUR AYIN HIOLA; NIRWAN JUNUS; NUVAZRIA ACHIR; KARLIN Z. MAMU; NURUL FAZRI ELFIKRI; MUHAMAD KHAIRUN KURNIAWAN KADIR (Universitas Mahasaraswati K. Mataram, 2024)
Marriage is the union of two people to form an eternal and happy family or household based on the Almighty God. Marriage is also an inner and outer bond between a man and a woman who become a husband and wife. The aim of this research is of course to find out the causes of non-reporting of marriages to the Population and Civil Registration Service. The type of research used is empirical research where the data source comes from facts in the field. The results of the research show that there are several things that cause marriages not to be reported, including negligence of the community itself, legal awareness and lack of socialization regarding marriage law and non-recording of marriage book registration numbers in the centralized SIAK system